2017
DOI: 10.1002/jbt.21960
|View full text |Cite
|
Sign up to set email alerts
|

Restorative effects of Chrysin pretreatment on oxidant–antioxidant status, inflammatory cytokine production, and apoptotic and autophagic markers in acute paracetamol‐induced hepatotoxicity in rats: An experimental and biochemical study

Abstract: Paracetamol (PC) is a widely used analgesic and antipyretic drug, but it leads to acute hepatotoxicity at high doses intakes. This study was aimed to investigate the effects of Chrysin (CR) on hepatotoxicity constituted at high doses of PC in rats. Rats were subjected to oral pretreatment of CR (25 and 50 mg/kg b.w.) via feeding needle for 6 days against hepatotoxicity induced by a single dose of PC (500 mg/kg b.w.) administered orally via feeding needles. Although PC increases lipid peroxidation and liver enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 29 publications
6
24
0
2
Order By: Relevance
“…This phenomenon supports that ROS and the resulting oxidative stress play a significant role in apoptosis 16 . Caspase‐3 can be described as a key mediator of apoptosis in mammalian cells because it initiates the apoptotic process by activating other caspase enzymes 27 . It causes DNA fragmentation, chromatin condensation, and protein breakdown 28 .…”
Section: Discussionmentioning
confidence: 65%
“…This phenomenon supports that ROS and the resulting oxidative stress play a significant role in apoptosis 16 . Caspase‐3 can be described as a key mediator of apoptosis in mammalian cells because it initiates the apoptotic process by activating other caspase enzymes 27 . It causes DNA fragmentation, chromatin condensation, and protein breakdown 28 .…”
Section: Discussionmentioning
confidence: 65%
“…Myocardial apoptosis, a common feature of DXR‐induced cardiotoxicity, has previously been demonstrated and our results are in agreement with these studies. Caspase‐3 has been known as marker of apoptosis in mammalian cells . In a similar study, it was observed that caspase‐3 activity increased in heart tissue after DXR application .…”
Section: Discussionmentioning
confidence: 71%
“…Caspase-3 has been known as marker of apoptosis in mammalian cells. [40] In a similar study, it was observed that caspase-3 activity increased in heart tissue after DXR application. [4] In this study, pretreatment of curcumin decreased caspase-3 activity compared with the DXR treated group.…”
Section: Immunohistochemical Analysismentioning
confidence: 88%
“…To overcome the side effects of the organ toxicity induced by chemotherapeutic drugs, safe cytoprotective antioxidants are necessary . Chrysin (CH) or 5,7‐dihydroxyflavone is a flavonoid present in various plants, bee propolis, and honey . It has multiple biological properties such as anticancer, antiapoptotic, antioxidant, anti‐inflammatory, and antihypertensive …”
Section: Introductionmentioning
confidence: 99%